Granulomatous rhinitis in a case of feline leishmaniasis - Arenales, Alexandre; Eckstein, Camila; Azevedo, Jaqueline [UNESP]; Reginaldo, Gisele M. S. [UNESP]; Lima, Valéria M. F. [UNESP]; Rozza, Daniela B. [UNESP]; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2018)
This is a case report of leishmaniasis with granulomatous rhinitis in a 2-year-old domestic cat. Clinically, an obstruction in the right nostril was observed, with cytopathological examination positive for Leishmania sp. Euthanasia was performed, and multinodular, diffuse and smooth pinkish lesions were observed in the mucosa of the nasal cavity. Microscopically, nodular lesions corresponded to an intense granulomatous inflammation with macrophages containing large numbers of Leishmania sp. amastigotes. Macrophages containing amastigotes were also occasionally observed in the popliteal lymph node, skin, and spleen. Based on immunohistochemistry, amastigotes were confirmed as Leishmania sp. and Leishmania sp. DNA was also detected by qPCR in lymph nodes samples. Although it is an uncommon manifestation, leishmaniasis should be considered as a differential diagnosis in diseases affecting the nasal cavity in domestic felines.
Keywords: Cat; Immunohistochemistry; Leishmaniasis; Nasal cavity